Staphylococcus aureus Bacteremias Following Liver Transplantation: A Clinical Analysis of 20 Cases [Expression of Concern] [Erratum] - Zhou J; Huang H; Liu S; Yu P; Wan Q (Dove Medical Press, 2020)
Zhou J, Huang H, Liu S, Yu P, Wan Q. Ther Clin Risk Manag. 2020;16:321. Due to a processing error the link for the British Medical Journal Open (BMJ Open) article described was missing. The link for the BMJ Open article has been provided here: http://dx.doi.org/10.1136/bmjopen-2018-024473.    Read the original article   Read the Expression of Concern